Value-sense complexes as the basis for the consolidation of socio-cultural capital of civilizations: the contents, the trends of transformations, potential of management - Shedyakov, V. E.; Шедяков, В. Є.; Шедяков, В. Е. (My University, 2016)
Socially responsible behaviour in the preservation and enhancement of socio-cultural capital is seen as a significant argument in competition between civilizations. Information dimension of interaction of cultural and civilizational worlds is analysed as the most important area of their competition. Strengthening and shaping of basic value-sense complexes are learned as a serious factor in the optimization of social order and development of society, in the final competitiveness between the cultural and civilizational worlds. It’s emphasizing, the power of humanity turned it into a factor commensurate with the nature. Accent the reflexive nature of the ongoing transformations greatly increases the potential for conscious intervention in the historical levels’ trends. However, the preservation and humanity itself, and the environment strictly require the recognition of the intrinsic self-value of cultural and civilizational worlds and consolidation of efforts for maintenance of the complex processes of self-organization and self-regulation.
Shedyakov V. E. Value-sense complexes as the basis for the consolidation of socio-cultural capital of civilizations: the contents, the trends of transformations, potential of management / V. E. Shedyakov // Актуальні проблеми філософії та соціології: Науково-практичний журнал / Голов. ред. Д. В. Яковлев; відпов. секретар І. В. Шамша; Міністерство освіти і науки України; Національний університет "Одеська юридична академія". - Одеса, 2016. - Вип. 13. - С. 91-94.
Keywords: value-sense complexes; socio-cultural capital; social management; ціннісно-смислові комплекси; соціокуль-турний капітал; соціальне управління; ценностно-смысловые комплексы; социокультурный капитал; социальное управление